2022
DOI: 10.1002/jcaf.22536
|View full text |Cite
|
Sign up to set email alerts
|

The joint effect of internal and external governance on earnings management and firm performance

Abstract: This study examines whether shareholders use internal governance mechanisms (i.e., manager compensation, shareholder rights protection at firm level) to substitute for weak external governance (i.e., investor protection mechanisms at country level) in restricting earnings management. We find that the impacts of internal governance on earnings management are stronger in countries with weak external governance. Examining the consequence of earnings management on firm performance, we find that internal governance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Indeed, most prior research has concentrated on the determinants of operational risk disclosure [66][67][68] or on the impact of other factors on operational risk disclosure [69][70][71][72], with various results. Other recent research has examined whether governance (or others) moderates a relationship between earnings management and firm performance [25,26]. Particularly, Ref.…”
Section: Empirical Review and Hypotheses' Developmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, most prior research has concentrated on the determinants of operational risk disclosure [66][67][68] or on the impact of other factors on operational risk disclosure [69][70][71][72], with various results. Other recent research has examined whether governance (or others) moderates a relationship between earnings management and firm performance [25,26]. Particularly, Ref.…”
Section: Empirical Review and Hypotheses' Developmentsmentioning
confidence: 99%
“…Previous studies have shown that higher-quality operational risk disclosure can improve firm performance and reduce the cost of equity [8,21,22], while other studies have found that risk disclosure can reduce the cost of capital and management's tendency to misreport earnings [23,24]. Other recent research has examined the moderator effect of corporate governance (or other factors) on the relationship between earnings management and firm performance [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…When corporate violations are reported in the media, managers may take a variety of defensive measures, such as changing internal controls, to mitigate the impact of negative publicity on the company (Duong et al, 2022). Internal supervision is an important part of a corporate own internal control.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Management entrenchment refers to the behavior of managers who choose to maintain their positions and maximize their own utility when their careers are threatened and pressured by dismissal or takeover (García‐Sánchez et al, 2020; Florackis & Ozkan, 2009). When corporate violations are reported in the media, managers may take a variety of defensive measures, such as changing internal controls, to mitigate the impact of negative publicity on the company (Duong et al, 2022). Internal supervision is an important part of a corporate own internal control.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…A literatura de gerenciamento de resultados, em sua maioria, analisa as empresas listadas em bolsa (e.g. Duong, Kang, & Salter, 2022;Owusu, Zalata, Omoteso, & Elamer, 2022). Isso acontece principalmente pelo fato de que existe uma exigência na qualidade das informações contábeis para tomada de decisão, com ênfase nos acionistas e demais agentes (Consoni, Colauto & Lima, 2017;Paulo & Mota, 2019;Rodrigues, Melo & Paulo, 2019) Frise-se que gerenciamento de resultados não é sinônimo de contabilidade fraudulenta, pois a primeira enquadra-se dentro da permissividade das normas contábeis, ainda que ambas possam dissimular a realidade em algum nível.…”
Section: Introductionunclassified